Climate change and fit and proper-testing in the Dutch financial sector. Issue 1 (2nd January 2019) - Palm-Steyerberg, Iris
Abstract : Dutch financial supervisors intend to embed climate-related risks more firmly in their supervision of Dutch financial institutions. As part of this process the Dutch supervisors are identifying which regulatory provisions could, and perhaps, should, form a basis for supervision on climate-related risks. The prudential authority, the Dutch Central Bank, or DNB, has selected "fostering a forward-looking and sustainable sector" as one of the three focus areas in its new Supervisory Strategy for 2018–2022. DNB will devote more attention to sustainability, including the impact of climate risks and policy on the financial sector. As part of this process, DNB will examine how sustainability risks can be included on a more systematic basis in its supervisory practices. This article poses the question whether fit and proper assessments of members of the management body can be regarded as one of the supervisory practices that financial supervisors may use to address climate-related risks.